Literature craft and voice Volume 2 Poetry - Delbanco, Nicholas; Cheuse, Alan. (Boston McGraw-Hill, 2010)
Reading a poem in its elements; Going further with reading; Writing about poetry; Words; Voice: tone, persona, and irony; Imagery and symbol; Figures of speech; Sound, rhyme and rhythm...
3 vols. planned Includes index
v. 1. Fiction -- v. 2. Poetry -- v. 3. Drama.
Keywords: Literatue; Văn học